1989
DOI: 10.1021/j100360a017
|View full text |Cite
|
Sign up to set email alerts
|

Study of the reaction chlorine monoxide + methyl peroxide .fwdarw. products at 300 K

Abstract: The first experimental study of the reaction CIO + CH302 -* products (1) is reported. The rate coefficient Aq and the product distributions were investigated in the modulated photolysis of Cl2/CH4/Cl20/02 mixtures. Reactants and products have been monitored by using UV-vis and Fourier-transform infrared gas-phase absorption spectroscopies. The value of A, was found to be equal to (3.1 ± 1.7) X 10"12 cm3 molecule"1 s'1 at 300 K and 240 Torr total pressure. The product channel forming ClOO and CH30 appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
58
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 2 publications
15
58
4
Order By: Relevance
“…The recommended expressions for the overall rate constant is based on the results of Helleis et al [566]. It is consistent with the room temperature measurements of Simon et al [1190] and Kenner et al [699]. The results of Kukui et al [743] for the overall reaction are in agreement with the recommendation at room temperature, but these values show a slight negative temperature dependence in contrast with the slight positive temperature dependence recommended here.…”
Section: -81supporting
confidence: 88%
See 2 more Smart Citations
“…The recommended expressions for the overall rate constant is based on the results of Helleis et al [566]. It is consistent with the room temperature measurements of Simon et al [1190] and Kenner et al [699]. The results of Kukui et al [743] for the overall reaction are in agreement with the recommendation at room temperature, but these values show a slight negative temperature dependence in contrast with the slight positive temperature dependence recommended here.…”
Section: -81supporting
confidence: 88%
“…This study, using a flash photolysis/long path ultraviolet absorption technique, is the most comprehensive study of this system, covering a wide range of temperature and pressure. These results are preferred over the results of earlier studies of the total bimolecular rate coefficient at low pressures by Clyne and Coxon [276], Clyne and White [302], and Clyne et al [289], and those of other studies reported by Hayman et al [560], Cox and Derwent [319], Simon et al [1191], Horowitz et al [599], and Horowitz et al [600]. The room temperature branching ratio are k 1 :k 2 :k 3 = 0.29:0.50:0.21.…”
Section: -81mentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, according to recent findings in this laboratory [35], the reaction between CH302 and C10 radicals t 18) CH302 + c10 * CH30 + cloz is quite fast (k18 = 3.1 x lo-'' cm3 molecule-' s-') and can readily compete with the self reaction of CH302 radicals which proceeds with a rate constant of 3.6 x cm3 molecule-' s-l 1361. The self reaction of CFC1202 radicals might be considerably faster than the self reaction of CH30z radicals (~c c~~o~+ c c~~o z = 1.6 x lo-'' cm3 molecule-' s-l [37]).…”
Section: (2')mentioning
confidence: 63%
“…Though early experiments 8,9 were unable to detect the weakly absorbing, unstable CH 3 OCl products from reaction 3b, later work using a discharge flow/mass spectrometer apparatus showed that this channel accounts for ∼23% of the reaction at typical stratospheric temperatures of ∼200 K. 7 Helleis et al obtained a channel-specific rate constant of (4.1 ( 1) × 10 -13 cm 3 molecule -1 s -1 . 7 These measurements indicate that channel 3b may have a significant impact on stratospheric chlorine cycles.…”
Section: Introductionmentioning
confidence: 99%